2005
DOI: 10.1017/s0265021503001017
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil added to hyperbaric bupivacaine for subarachnoid block in Caesarean section

Abstract: The addition of sufentanil 5.0 and 7.5 microg to hyperbaric bupivacaine provided adequate anaesthesia for Caesarean section and good postoperative analgesia. Pruritus was the most common side-effect and had a significantly higher incidence when a dose of sufentanil 7.5 microg was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…Braga et al [19] reported that the analgesia duration was lengthened significantly for groups that used 5 µg and 7.5 µg of sufentanil compared to control or 2.5 µg of sufentanil group, and Demiraran et al [7] reported a similar result as our study, showing a significantly longer analgesic duration for groups that used 1.5 µg, 2.5 µg, and 5.0 µg of sufentanil than that of control group. The present study showed that effective analgesic duration, measured using PCA connecting time, was 218.5 ± 71.8 minutes for 2.5 µg sufentanil, 282.3 ± 110.9 minutes for 5 µg.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Braga et al [19] reported that the analgesia duration was lengthened significantly for groups that used 5 µg and 7.5 µg of sufentanil compared to control or 2.5 µg of sufentanil group, and Demiraran et al [7] reported a similar result as our study, showing a significantly longer analgesic duration for groups that used 1.5 µg, 2.5 µg, and 5.0 µg of sufentanil than that of control group. The present study showed that effective analgesic duration, measured using PCA connecting time, was 218.5 ± 71.8 minutes for 2.5 µg sufentanil, 282.3 ± 110.9 minutes for 5 µg.…”
Section: Discussionsupporting
confidence: 87%
“…Braga et al [19] reports the higher sedation frequencies in patients with increasing sufentanil dosages and although the present study confirms the significant increase in the sedation with increasing sufentanil dosage, there was no excessive sedation in any patient who did not wake at light arousal. In the present study, although nausea was significantly more frequent in groups that used sufentanil, there was no significant difference between Group 2 and 3.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The duration of effective analgesia is improved by the addition of sufentanil 5.0 and 7.5 µg according to Braga Ade et al [18] and it is effectively prolonged by the addition of sufentanil 1.5, 2.5 and 5.0 µg. Comparison of fentanyl and sufentanil [2] demonstrated that the duration of effective analgesia was significantly increased in the sufentanil 2.5 and 5.0 µg groups in contrast with that of the control group and the fentanyl 10 µg group.…”
Section: Discussionmentioning
confidence: 99%
“…We used a slightly higher dosage of intrathecal sufentanil to reduce local anaesthetic requirement and to provide prolonged analgesia, and our patient did not require any epidural top-ups during the surgery 70. This may be advantageous as compared to the use of intrathecal fentanyl, where frequent top ups were required 26,42.…”
Section: Discussionmentioning
confidence: 97%